2020
DOI: 10.1089/thy.2019.0255
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 3-Iodothyronamine Rescues the Entorhinal Cortex from β-Amyloid Toxicity

Abstract: Background. A novel branch of thyroid hormone (TH) signaling is represented by 3iodothyronamine (T 1 AM), an endogenous TH derivative that interacts with specific molecular targets, including trace amine associated receptor-1 (TAAR 1 ), and induces pro-learning and antiamnestic effects in mice. Dysregulation of TH signaling has long been hypothesized to play a role in Alzheimer's disease (AD). In the present investigation, we explored the neuroprotective role of T 1 AM in beta amyloid (Aβ)-induced synaptic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 78 publications
0
26
0
Order By: Relevance
“…Indeed, the results obtained after testing the ability of SG-2 to restore LTP in mhAPP mouse showed that this molecule is also able to reproduce the protective effect of T1AM against Aβ toxicity at the level of the entorhinal cortex (EC). This finding may also strengthen the role of TAAR1 as a possible drug target to ameliorate cognitive dysfunction in AD patients [35]. As a further expansion of this preliminary study, since protein homeostasis is crucial to sustain synaptic long-term plasticity and counteracting AD pathology, in future studies we will direct our attention to evaluate whether T1AM and SG-2 are also able to produce SIRT6-dependent activation of autophagy in the EC of mhAPP mice.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Indeed, the results obtained after testing the ability of SG-2 to restore LTP in mhAPP mouse showed that this molecule is also able to reproduce the protective effect of T1AM against Aβ toxicity at the level of the entorhinal cortex (EC). This finding may also strengthen the role of TAAR1 as a possible drug target to ameliorate cognitive dysfunction in AD patients [35]. As a further expansion of this preliminary study, since protein homeostasis is crucial to sustain synaptic long-term plasticity and counteracting AD pathology, in future studies we will direct our attention to evaluate whether T1AM and SG-2 are also able to produce SIRT6-dependent activation of autophagy in the EC of mhAPP mice.…”
Section: Discussionmentioning
confidence: 57%
“…Previous experiments showed that mhAPP slices, perfused with ACSF enriched with 5µM T1AM, regained LTP capacity after high frequency stimulation induction protocol (HFS) [18]. Notably, in a very recent work Accorroni et al demonstrated that in the same experimental model co-administration of 5 nM EPPTB, a selective TAAR1 antagonist, was able to revert the rescuing effects of T1AM on LTP [35], suggesting a role of TAAR1 as a possible drug target to ameliorate cognitive dysfunction in AD patients. Since SG2 is a recently developed T1AM analog endowed of almost comparable TAAR1 agonist properties (EC50 SG-2 = 240 nM; EC50 T1AM = 189 nM) [36], we hypothesized that it may have a similar effect, and we decided to administer this compound in the perfusion medium at different concentrations.…”
Section: Sg-2 Rescues Ltp In Happ-j20 Mouse Model Of Ad At the Level mentioning
confidence: 99%
“…Furthermore, SIRT1, 3, 4, and 6 can also regulate glucose and fat homeostasis [82], thus representing a possible "entry point" for drugs simultaneously addressing metabolic syndrome and ageing. Intriguingly, T1AM showed (neuro)protective actions in several cell and rodent models, including seizure-related excitotoxic damage, altered autophagy, amyloidosis, and ischemia-reperfusion injury [61,[88][89][90][91].…”
Section: Genomic Regulation Of Metabolismmentioning
confidence: 99%
“…It thus follows that the selective augmentation of some of T1AM actions can represent an attractive strategy for the treatment of metabolic disturbances [97]. Substantial data described in the last two decades provide compelling evidence of the action of T1AM as a multitarget modulator of metabolism and behavior in several experimental models and pathophysiological conditions [41,44,46,89,90], raising hope for increasing therapeutic option in the treatment of a wide variety of diet-and age-related diseases, such as obesity and neurodegeneration.…”
Section: Therapeutic Implications and Development Directionmentioning
confidence: 99%
“…3-iodothyronamine (T1AM) is a metabolite product of the thyroid hormones (TH), which exert an opposite physiological function of classical TH such as a decrease of body temperature and metabolic rate in rodents [3]. Several studies have shown that T1AM is presumed to act on various organs and different receptors rapidly [4].…”
Section: Introductionmentioning
confidence: 99%